An Evaluation of language Ontology Web Based Assessment System - Taurayi Rupere (International Journal of Evaluation and Research in Education (IJERE), 2013)
The field of e-learning has improved tremendously in the past decade with the invention of all kinds of e-leaning systems contributing to the quality of education. The undertaken research seek to improve web assessment systems which are limited to multiple choice type of assessment which is summative assessment that does not have a feedback section to students hence promote limited learning. The proposed system uses ontologies to promote formative assessment with a feedback loop to the students. The structured type of questions are now implemented in web assessment systems instead of using multiple choice type of questions which have limitations in terms of functionality when it comes to marking textual answers due to wide variety of words that can mean the same thing. The designed system was implemented using an ontology based dictionary which generates all possible solution for a particular question and uses aspects of artificial intelligence. The system was applied to two primary schools students doing grade 4 levels. Students wrote a test that was marked by both the system and teacher. Results from the study showed that the system marks as close to the human examiner and is the ideal assessment and marking if implemented well.DOI: http://dx.doi.org/10.11591/ijere.v2i3.2257